Evolution of Research Streams and Future Research Directions in Accounting Education: Quantitative Systematic Literature Review - Cao, June; Kristanto, A.B.; Gu, Z. (2024)
This study comprehensively analyzes the landscape of accounting education research and constructs the agenda for future studies. We are specifically interested in investigating the current state of accounting education research and identifying areas that require further attention for its development. We employ a quantitative systematic literature review focusing on 673 academic articles from top-tier accounting journals. The study applies various bibliometric analyses, including co-citation, bibliographic coupling, keyword co-occurrence, topic burstiness, and thematic mapping, using HistCite, VOSviewer, CiteSpace, and R Bibliometrix software. Through rigorous examination, we identify three prominent research streams: (1) accounting pedagogy, (2) competencies, and (3) ethics. Furthermore, each stream discusses specific distinctive themes. This study suggests future investigations on leveraging the accounting education role in pursuing environmental sustainability and embracing technology to improve student engagement in post-pandemic learning.